2011
DOI: 10.1055/s-0031-1283148
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin Blocks Advanced Glycation End Products-elicited Reduction of Macrophage Cholesterol Efflux by Suppressing NADPH Oxidase Activity via Inhibition of Geranylgeranylation of Rac-1

Abstract: Adenosine triphosphate-binding membrane cassette transporter A1 (ABCA1) and ABCG1 play a crucial role in macrophage cholesterol efflux, which is a novel therapeutic target for atherosclerosis. Advanced glycation end products (AGE) and their receptor RAGE axis is involved in accelerated atherosclerosis in diabetes as well. However, the role of AGE-RAGE axis in macrophage cholesterol efflux is not fully understood. We examined here whether AGE-RAGE axis could impair cholesterol efflux from human macrophage cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 13 publications
1
15
0
3
Order By: Relevance
“…AGEs-RAGE-mediated signal transductions are involved in NF-kB-associated mediators including p38MAPK, Rho GTPases, and Rac-1 [38][39][40]. Rebalancing ROS and antioxidant defenses can inhibit AGE-induced reduction of THP-1 macrophage cholesterol efflux via inhibition of geranylgeranylation of Rac-1 [41]. Our findings demonstrate that IRAK-1 is an intertwined modulator between AGEs-and P.g LPS-triggered dysregulation of cholesterol metabolism although AGEs, itself, cannot mediate the P.g LPS tolerance model.…”
Section: Discussionmentioning
confidence: 99%
“…AGEs-RAGE-mediated signal transductions are involved in NF-kB-associated mediators including p38MAPK, Rho GTPases, and Rac-1 [38][39][40]. Rebalancing ROS and antioxidant defenses can inhibit AGE-induced reduction of THP-1 macrophage cholesterol efflux via inhibition of geranylgeranylation of Rac-1 [41]. Our findings demonstrate that IRAK-1 is an intertwined modulator between AGEs-and P.g LPS-triggered dysregulation of cholesterol metabolism although AGEs, itself, cannot mediate the P.g LPS tolerance model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we demonstrated that AGEs reduce adenosine triphosphate-binding membrane cassette transporter A1 (ABCA1) and ABCG1 levels in THP-1 cells and inhibit cholesterol efflux from THP-1 macrophages to apolipoprotein (apo) AI and HDL cholesterol, respectively (41). These findings suggest the involvement of the AGE-RAGE axis in impaired re-verse cholesterol transport in diabetes and accelerated foam cell formation within the atherosclerotic lesions (41,42).…”
Section: Cvdmentioning
confidence: 95%
“…Соответственно, AGE ингибируют выделение холестерина из макрофагов в аполипопротеин (apo) АI и липопротеиды высокой плотности. Это подтверждает роль AGE и их рецепторов при нарушении транспорта холестерина и ускорении формирования пенистых клеток внутри атеросклероти-ческих бляшек [25].…”
Section: конечные продукты гликированияunclassified